Inhibitory Test of Turmeric Juice and Young Coconut Water Against Clostridium Perfringens Bakteri Bacteria: Uji Daya Hambat Air Perasan Kunyit dan Air Kelapa Muda Terhadap Bakteri Clostridium Perfringens - Absari, Eki Puji; Rini, Chylen Setiyo (Indonesian Journal of Innovation Studies, 2020)
Medicinal plants are plants that contain ingredients that can be used for treatment and the active ingredients can be used as synthetic medicinal ingredients. One of the medicinal plants that is often used is turmeric (Curcuma longa). In addition, there is young coconut (Cocos nucifera) which is a plant native to the tropics, has water on the inside of young coconuts and can be consumed without going through processing. This study aims to determine the potential of the combination of turmeric juice with young coconut water in inhibiting Clostridium perfringens bacteria. This study used 5 concentrations, namely 25%, 50%, 75% and 100% and the combination of turmeric juice with young coconut water, namely 25%: 75%, 50%: 50% and 75%: 25%. The concentration of 100% extract of turmeric juice and young coconut water was the best concentration to form an inhibitory zone against the bacterium Clostridium perfringens of 32.66 mm and 14 mm.